1990
DOI: 10.1099/00221287-136-3-441
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Studies on Methylotrophic Bacteria by 5S Ribosomal RNA Sequencing

Abstract: Nucleotide sequences of 5s ribosomal RNA (rRNA) isolated from 19 strains of Gram-negative methylotrophic bacteria were determined. Comparison of these sequences allowed construction of a tentative phylogenetic tree and showed that the bacteria analysed belong to the Proteobacteria and fell into several clusters, including obligate methanotrophs, obligate methylotrophs and several groups of facultative methylotrophs. Taxonomic relations between methylotrophic and non-methylotrophic bacteria are discussed, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…On the basis of their genomic properties, all known type II methanotrophs represent a very tight group. The results of analysis of 5S rRNA (Bulygina et al, 1990) and 16S rRNA (Bratina et al, 1992) sequences indicated that these methanotrophs form a distinct and tight cluster, within the α-subclass of the Proteobacteria, which is separate from the rest of the serinepathway methylotrophs. Subsequent investigations of the functional genes encoding key enzymes in the methane-oxidation pathway of type II methanotrophs provided further proof of this cluster homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of their genomic properties, all known type II methanotrophs represent a very tight group. The results of analysis of 5S rRNA (Bulygina et al, 1990) and 16S rRNA (Bratina et al, 1992) sequences indicated that these methanotrophs form a distinct and tight cluster, within the α-subclass of the Proteobacteria, which is separate from the rest of the serinepathway methylotrophs. Subsequent investigations of the functional genes encoding key enzymes in the methane-oxidation pathway of type II methanotrophs provided further proof of this cluster homogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…They include the prosthecate bacteria, and the genera Caulobacter and Aquaspirillum. However, a number of bacteria utilizing C1 compounds, such as the budding bacteria, Hyphomicrobium, and a range of methanol-oxidizing "methylotrophs" are distributed in both the alpha and beta subclasses (Bulygina et al 1990;Stackebrandt et al 1988a) and even some obligate methylotrophs (e.g., Methylococcus capsulatus and Methylomonas methanica) belong in the gamma subclasses (Tsjui et al 1990). Therefore it may be important that methanol-utilizing bacteria obtain their substrate not only as a consequence of pectin decomposition but as a result of incomplete methane oxidation by methanotrophs and in distinct ecological niches (Naursaraev and Zavarzin 1972;Zavarzin 1986).…”
Section: F~gmentioning
confidence: 98%
“…Integrating PLFA phenotype and phylogenetic relationships Taxonomic relationships for methylotrophic eubacteria have been reported utilizing 16s rRNA , 5s rRNA (Ando et al 1989;Bulygina et al, 1990), DNA base composition with DNA-DNA homologies (Urakami et al, 1985;Hood et al, 1987), as well as multivariate analyses of characters based on morphology, physiology and biochemistry (Green & Bousfield, 1982;Jenkins & Jones, 1987). Most of these studies have not used the same strains discussed in this work; hence, integration of relationships is difficult.…”
Section: Plfa Projles and Phenotype Stabilitymentioning
confidence: 99%
“…The systematics of the methylotrophs is currently based on nucleic acid sequencing assays Bulygina et al, 1990). This present study reports membrane fatty acid profiles for 17 methylotrophic eubacterial strains of which many have been placed on 16s rRNA phylogenetic trees .…”
Section: Introductionmentioning
confidence: 99%